2016
DOI: 10.3389/fpls.2016.01627
|View full text |Cite
|
Sign up to set email alerts
|

An S-adenosyl Methionine Synthetase (SAMS) Gene from Andropogon virginicus L. Confers Aluminum Stress Tolerance and Facilitates Epigenetic Gene Regulation in Arabidopsis thaliana

Abstract: Candidate clones which conferred Al tolerance to yeast transformants (TFs) were obtained from a cDNA library derived from a highly Al-tolerant poaceae, Andropogon virginicus L. One such clone, AL3A-4, encoded an S-adenosyl methionine synthetase (SAMS) gene. A full-length cDNA was obtained by 5′-RACE, designated AvSAMS1, and introduced into Arabidopsis thaliana to investigate its biological functions under Al stress. Two TF plant lines both showed higher tolerance than the Col-0 ecotype (non-TF) not only for Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 46 publications
(49 reference statements)
0
17
0
1
Order By: Relevance
“…Overexpression of the AvSAMS1 resulted in changes both in DNA and histone H3 methylation after plant exposure to Al. More interestingly, there were differences in the demethylation and methylation patterns at different positions in the promoter and coding regions of this gene (Ezaki et al, 2016).…”
Section: Epigenetic Mechanism Involved In Aluminum Toxicitymentioning
confidence: 89%
“…Overexpression of the AvSAMS1 resulted in changes both in DNA and histone H3 methylation after plant exposure to Al. More interestingly, there were differences in the demethylation and methylation patterns at different positions in the promoter and coding regions of this gene (Ezaki et al, 2016).…”
Section: Epigenetic Mechanism Involved In Aluminum Toxicitymentioning
confidence: 89%
“…SAMS genes from multiple plant species have been validated to be involved in plant adaptation to multiple abiotic stresses. Overexpressing SAMS genes results in increased tolerance to drought (Kim et al, 2015), salinity (Kim et al, 2015; Ma et al, 2017), alkali (Gong et al, 2014), Al toxicity (Ezaki et al, 2016) and oxidative stresses (Ma et al, 2017). Like in MfSAMS1 transgenic tobacco plants with increased freezing and chilling tolerance (Guo et al, 2014), overexpression of MfSAMS1 resulted in enhanced chilling tolerance in transgenic stylo plants.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al (2003) found that the expression of the SAMS gene from Suaeda salsa is induced under NaCl stress (Ma et al 2003). Recently, it has been reported that the AvSAMS gene confers aluminum stress tolerance and facilitates epigenetic gene regulation (Ezaki et al 2016). SAMS is therefore known to play roles in various plant defense systems.…”
Section: Discussionmentioning
confidence: 99%